2023
DOI: 10.1002/smll.202303221
|View full text |Cite
|
Sign up to set email alerts
|

Porous and Partially Dehydrogenated Fe2+‐Containing Iron Oxyhydroxide Nanosheets for Efficient Electrochemical Nitrogen Reduction Reaction (ENRR)

Abstract: The design and development of efficient catalysts for electrochemical nitrogen reduction reaction (ENRR) under ambient conditions are critical for the alternative ammonia (NH3) synthesis from N2 and H2O, wherein iron‐based electrocatalysts exhibit outstanding NH3 formation rate and Faradaic efficiency (FE). Here, the synthesis of porous and positively charged iron oxyhydroxide nanosheets by using layered ferrous hydroxide as a starting precursor, which undergoes topochemical oxidation, partial dehydrogenated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…The eNRR performance achieved in this work is comparable to many of the reported results under ambient conditions in recent years (Table S8, Supporting Information). [ 3,45–48 ] Thus, based on the above analysis, the mass transfer enhancement and HER inhibition effects could be fully demonstrated using the Ru/C and Fe/g‐CN catalytic systems as well, indicating the excellent general applicability of the BBMR.…”
Section: Resultsmentioning
confidence: 84%
“…The eNRR performance achieved in this work is comparable to many of the reported results under ambient conditions in recent years (Table S8, Supporting Information). [ 3,45–48 ] Thus, based on the above analysis, the mass transfer enhancement and HER inhibition effects could be fully demonstrated using the Ru/C and Fe/g‐CN catalytic systems as well, indicating the excellent general applicability of the BBMR.…”
Section: Resultsmentioning
confidence: 84%
“…11 Alternatively, low-cost ENRR catalysts based on metal oxide (Fe 2 O 3 , W 18 O 49 , BiOBr, etc. ), [12][13][14] metal (oxy)hydroxide, 15,16 metal-organic-framework (MOF) and MOF-derived materials, [17][18][19][20][21] singe atoms, [22][23][24] metallenes 25 and carbon (both, doped and undoped) [26][27][28][29] have been reported; however, with poor stability and activities. 30 Therefore, there is an urgent need for the design and development of low-cost, robust ENRR catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…16−18 Due to the scarcity and high cost of noble metals, 19,20 iron (Fe) appeals to researchers in recent years owing to its low cost and promising high catalytic ability for nitrogen reduction reaction (NRR). 21 Wang et al 22 found that a single Fe atom anchored on the anatase TiO 2 (001) surfaces shows wellbalanced activity for N 2 fixation and NH 3 dissociation in NRR, based on first-principle calculations. Toprek et al 23 studied the optical properties of anatase TiO 2 (101) upon introducing one Fe atom on the surface and observed enhanced visible-light absorption.…”
Section: Introductionmentioning
confidence: 99%